Highly Aggressive CD4-Positive Mast Cell Leukaemia (Leukaemic Variant) Associated with Isolated Trisomy 19 and Hemophagocytosis by Neoplastic Mast Cells: A Case Report with Challenging Experience and Review - Dina Sameh Soliman; Ahmad Al-Sabbagh; Feryal Ibrahim; Amna Gameil; Mohamed Yassin; Halima El-Omri (Case Reports in Hematology)
Background. Mast cell leukaemia is a unique disease among hematopoietic neoplasms, being one of the rarest leukaemia subtypes. In addition, its prompt diagnosis is usually challenging. This is due to its heterogeneity in clinical presentations and cytomorphological and immunophenotypical features together with potential associations with other hematologic neoplasms which can complicate the condition and delay accurate diagnosis. To the best of our knowledge, this is the first case report of CD4-positive mast cell leukaemia. Case Presentation. A 39-year-old male presented with acute onset of fever, abdominal pain, and generalized body aches of two-week duration. Peripheral blood smear showed circulating blasts (13%) with coarsely basophilic granulation. Bone marrow (BM) aspirate showed extensive infiltration with immature mast cells of blast-like morphology with trilineage dysplasia and evident hemophagocytic activity exhibited by histiocytes and neoplastic mast cells. BM biopsy was diffusely infiltrated with many atypical mast cells positive for CD45, CD117, mast cell tryptase, CD25, and CD4 with partial positivity for CD7 and CD30. Cytogenetics showed an abnormal karyotype: 47, XY, +1947, XY, +19[13]/46, XY[9]. Molecular analysis revealed a KIT D816V mutation consistent with a diagnosis of systemic mastocytosis, mast cell leukaemia. Conclusion. The expression of T-cell associated markers by abnormal mast cells is well documented; however, CD4 and CD7 expression have not previously been described in association with mast cell leukaemia. Coexpression of CD2, CD4, CD7, and CD30 by the mast cells particularly in skin lesions may provoke misinterpretation as a cutaneous T-cell neoplasm. To the best of our knowledge, this is the first report of CD4-positive mast cell leukaemia. Moreover, hemophagocytic mast cell leukaemia is a very rare morphologic variant, and possible correlation between this finding and expression of CD4 by neoplastic mast cells is a topic for further investigation.